Desert king's surprise love-child - Williams, Cathy (Harlequin presents, 2021)
"Everything changed the minute Crown Prince Abbas was suddenly forced to assume the role of ruler. When chance reunites him with the woman he had to leave behind, he learns two things: she's still utterly enchanting and he's a father! Georgie's reeling from the shock of discovering that Abe's royalty when he insists they marry. The passion that brought them together is undeniable but so is the pain of his swift exit from her world. Abe wants her as his queen...but does he truly want her as his wife?" -- Page [4] cover.